Congenital Bladder Diverticulum in Adults: A Case Report and Review of the Literature - Rawad Abou Zahr; Khalil Chalhoub; Farah Ollaik; Joe Nohra (Case Reports in Urology)
A 37-year-old male patient presented to the emergency department with fever, gross hematuria, and irritative lower urinary tract symptoms. Investigations revealed the presence of a large left bladder diverticulum superior and lateral to the left ureteral orifice without bladder outlet obstruction. Bladder diverticula in adults almost always present in the setting of bladder outlet obstruction. The finding of a congenital bladder diverticulum in an adult represents a rare clinical entity.